LQR control of interleaved double dual boost converter for electrical vehicles and renewable energy conversion - J. S. V. Siva Kumar; P. Mallikarjunarao (Indonesian Journal of Electrical Engineering and Computer Science, 2019)
The automobile industry is one of the major industries that are having its new innovations at a great pace according to the requirements of the day-to-day life. Due to the usage of conventional vehicles on a large scale which usually use petroleum products as fuel, is leading to a vast environmental effect, mainly due to the emission of greenhouse gases. So in order to reduce the ill effects of the greenhouse gas emissions great efforts are being put in   manufacturing of electrical vehicles. Among the currently available greenhouse technologies the fuel cell provides high energy density in spite of its expenses. So, in this aspect a required mechanism has to be adopted to make it energy efficient and affordable. In order to overcome the drawback of fuel cell i.e. low output voltage, the boost converters are to be used and to be more precise Non-isolated Interleaved Double Dual Boost (IDDB) converters are recommended which makes it efficient and also the reduction of overall vehicle weight can be achieved. The LQR control technique is applied in this work to make the transient response of the fuel cell powered IDDB converter for various load conditions effective. The verification of results is done with simulation techniques using MATLAB/Simulink.